Validation of HPLC-MS Method in Positive Ion Mode for Estimation of Phenytoin in Human Plasma Using Phenytoin D10 as Internal Standard - Alegete, Pallavi; Kancherla, Prasad; Keesari, Srinivas; Rao Yedlapalli, Siva Sanker; Boodida, Sathyanarayana (Asian Journal of Chemistry, 2017)
A high performance liquid chromatography mass spectrometric method for the estimation of phenytoin, in human plasma in positive ion mode was developed and validated using phenytoin D10 as internal standard (IS). Sample preparation was accomplished by solid-phase extraction technique. The eluted samples were chromatographed on Zorbax Eclipse XDB-Phenyl 4.6 × 75 mm, 3.5 μm (Make: Agilent Technologies) column using a mobile phase consisting of HPLC grade acetonitrile: 0.1 % formic acid (80:20 v/v). The method was validated over a concentration range of 101.253 to 10074. 937 ng mL-1 for phenytoin. This validation report provides the results of selectivity, matrix effect, sensitivity determinations, precision and accuracy data, recovery and dilution integrity along with all pertinent documentation. An open label, balanced, randomized, two-treatment, two-period, two-sequence, cross-over, single oral dose bioequivalence study of phenytoin sodium 100 mg capsules (3 × 100 mg, a total of 300 mg) of Green Evolution Laboratories, India comparing with phenytoin sodium flynn 100 mg hard capsules (3 × 100 mg, a total of 300 mg) of Flynn Pharma Ltd, Alton House, Ireland in healthy, human adult subjects, under fasting conditions was conducted. The 90 % confidence intervals were calculated for the Cmax, AUC(0-t) and AUC(0-¥), giving values between 96.26-110.38 % demonstrating the bioequivalence of the two formulations.